Hubungan Kualitas Makanan dan Tingkat Pelayanan terhadap Sisa Makanan Santri di Pondok Pesantren Al-Mubarokah - Alivia Dwi Shinta; Lilia Faridatul Fauziah (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
From menu design to food delivery, the execution food consists of a number of tasks. Food management is focused on customer happiness with food quality and service, and as food waste is a good indicator of customer satisfaction, it may be used to gauge how well food management is working. Finding out how meal quality and service level relate to students' food waste is the aim of this study. cross-sectional temporal approach combined with analytical research methodology. Using a stratified random sampling approach, the study's sample consisted of 112 female students, out of the total 156 respondents. Food waste is a dependent variable, while food quality and service quality are independent factors. A statistical test of spearman's correlation is used in the study analysis. According to the study's findings, the majority of female students were unhappy with the caliber of the meal and the degree of service. Regarding leftovers, the majority of female students left food in a variety of areas. There was a significant correlation between food quality and food waste, according to the findings of the food quality statistical test (p-value = 0.002 < 0.05), and between service level and food waste (p-value = 0.000 < 0.05). According to the study's findings, food waste decreases with increasing meal quality and service, whereas it increases with decreasing food quality and service.